MUNICIPAL SOLID WASTE INDICATORS: A CASE STUDY IN TUPA/SP - Dadario, Natalia [UNESP]; Destro, Guilherme Eduardo [UNESP]; Rizk, Maria Cristina [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2020)
Sewerage services provided by the municipality concerning the management of municipal solid waste (MSW) interfere directly with the environment and the daily life of cities. Numerous municipalities in Brazil has been facing MSW management problems, and a lack of indicators to assist in the evaluation of such systems hinders decision-making for technical and operational improvement of the services provided. Accordingly, this article assessed the MSW management system of Tupa/SP through the application of Management Quality Index and MSW Management, proposed by Gothardo and Linhares (2016), which could serve as a benchmark for planning and operational improvement of MSW management services in the municipality. The evaluation of this index applied in the studied municipality has revealed that there is room for improvement, in particular to indicators for storing and treating solid urban waste and political instruments. Moreover, it has been noted that the application of the studied content was an important tool for identifying the problems and proposing solutions, which may be considered an instrument to assist public administrations to enhavnce the MSW management system.
Keywords: Municipal Solid Waste; Index; Municipal Management; Waste Management